Pengaruh Motivasi, Pengetahuan dan Kepemimpinan Terhadap Minat Mahasiswa Nabung Saham (Studi Kasus Pada Program Studi Perbankan dan Keuangan Politeknik Negeri Balikpapan Tahun 2019) - Totok Ismawanto; Hasto Finanto (P3M Politeknik Negeri Bali, 2019)
Abstract The main objective of this study was to determine whether there was a significant effect of motivation, knowledge, and leadership on students' interest in saving stocks. The problem behind this research is whether the leadership of the management of the Balikpapan State Polytechnic Banking and Finance study program can encourage the growth of students' interest in investing through stock savings. The research method uses a survey method, with data collection techniques through questionnaires, interviews, documentation and observation. This type of research is quantitative research with sampling techniques using simple random sampling. The sample students were 100 people from the total population of 166 Banking and Finance study programs. Data analysis using statistical tests, namely correlation coefficient, multiple regression, F test and t test. Based on the results of the analysis, it was concluded that motivation, knowledge, and leadership together had a significant effect on students' interest in saving stocks. The leadership variable has the most dominant influence on student interest in stock saving investments, indicated by the results of t test of 7.077, compared to motivation and knowledge variables, each of which was 3.379 and 6.635. From the documentation, students who have an account to transact on the capital market are 84 people, or 51% of the total students of the Balikpapan State Polytechnic Banking and Finance study program. Keywords: Motivation, Knowledge, Leadership, Interest, Investment